HyperArc multiple brain metastases report - Gloi, Aime M. (International Journal of Research in Medical Sciences, 2024)
This report presents the initial clinical experience with HyperArc, a novel modality that incorporates a non-coplanar, arc-based multileaf collimator (MLC) and automated treatment optimization and dose delivery. The study focuses on a patient who had previously received whole-brain radiotherapy. The effectiveness and challenges of HyperArc were assessed by evaluating various quality indices for stereotactic radiosurgery within the RTOG protocol, as well as an additional measure of toxicity in the form of the V12Gy volume. The HyperArc plan achieved quality indices of 1.13, 4.58, and 0.88 for CI, GI, and CIPaddick, respectively. The mean ICRU83 value was 0.17±0.01, and it remained consistent across all six lesions. The V12Gy value was equal to 8.76 cc. The HyperArc plan successfully met the constraints for organs-at-risk (OAR). These results suggest that HyperArc is a suitable modality for treating multiple brain metastases, as indicated by the quality indices and metrics. Additionally, V12Gy is a valuable indicator for assessing low-dose spillage.